Bowling Together: Scientific Collaboration Networks of Demographers at European Population Conferences - Guy Abel; Emilio Zagheni; Valeria Bordone; Raya Muttarak (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2018)
Exploiting a unique database of metadata for papers presented at six European Population Conferences (EPC) for the years 2006-2016, this paper explores: 1) development of research in population studies; 2) trends and patterns of scientific collaboration networks among demographers; and 3) gender differences in demographic research. The data are organised in a panel format whereby each author, institution and country are linked across the six conferences. We find that collaboration among demographers has increased substantially over the past ten years. While there is no gender disparity in the likelihood of co-authoring a paper, men are significantly more likely than women to collaborate with authors from other institutions. Likewise, the fields of research vary considerably by gender where women are particularly overrepresented in the subfield 'fertility and family' whereas men dominate the subfield 'data and methods'. Compared to other subfields, research on 'data and methods' is more likely to involve collaboration across multiple institutions. With respect to collaboration patterns at the institutional level, a chord diagram plot shows that scientific collaborations across institutions are more common between institutions sharing geographical proximity. Finally, using network centrality measures, we identify key demographic research institutes which play a role in driving demographic research in Europe.
Keywords: 300; Centrality measures; demographers; gender; networks; population studies; scientific collaboration